EVALUASI BIMBINGAN KONSELING DI SEKOLAH DENGAN PENDEKATAN GOAL FREE EVALUATION - Narti, Sri (Universitas Muhammadiyah Magelang, 2010)
Evaluation can be formal or informal. Formal evaluation sought to determine whether a series of guidance activities carried out according to plan programs that have been done in order to achieve certain concrete goals, indeed achieve the expected effects. The core part of formal evaluation lies in the determination and implementation of appropriate procedures, namely whether a sequence of activities that have been implemented guidance clearly produce significant changes in student behavior, according to various criteria that is consistent with guidance service goals.Informal evaluation is a process of assessment of the effectiveness of counseling services without holding on to a scientific design and without using methods and tools specified in the design. Informal evaluation is usually done while walking and is a mental activity a person who is performing a task. For example if school counselors provide career guidance to groups of students in grade school, he opened ears and eyes to get an indication about the efficiency and effectiveness of all activities undertaken jointly with the guidance of the students in the class.Evaluation guidance counseling with a goal free evaluation approach is not completely free from the goal, but only out of special purposes. This model considers only the general objectives to be achieved. Keep in mind how outsiders judge the program not only to know what the quality, but also knowing what should be done, what was done in all parts, on all that has been produced, intentionally or unintentionally. The latter is the task of goal-free evaluators who do not know the purpose of the program.